IDENTIFIKASI INDENTITAS BUDAYA DALAM IKLAN VISIT JAPAN MENGGUNAKAN PENDEKATAN SEMIOTIKA - Denta Mandra Pradipta Budiastomo; Nukke Sylvia; Supriyadi Gunawan (Narada : Jurnal Desain dan Seni, 2019)
Japanese tourism campaign with the theme Where tradition meets the future success in advertising Japanese tourism itself. This advertisement invites tourists to feel the traditional and modern side in Japan. Behind that success is certainly a question, what are the signs in the ad that represent Japanese cultural identity. Departing from the above problems, researchers used Roland Barthes's Semiotics approach which aims to examine the signs and meanings of the success of these advertisements.Researchers limit the problem to only identifying signs of cultural identity for each scene that lasts three minutes. The researcher clarified between signifier, signified, denotation and connotation meaning to find out what cultural identity each scene contained. Hopefully from the results of this study it can be concluded that many tourism advertising materials insert cultural identity.